A Perhaps Less Halakic Jesus and Purity - Kazen, Thomas (Journal for the study of the historical Jesus, 2016)
Purity practices during the first century ce were widespread in Judaea and Galilee as part of everyday life and not limited to concerns relating to the temple cult. Developments in key water rites were partly triggered by concepts of graded impurity, to which an understanding of defilement via food also belonged. Certain rabbinic characteristics represent later developments and cannot be assumed for the time of Jesus. Hand impurity did not originate as a rabbinic decree to protect tĕrûmâ, and accusations against Pharisees for setting aside Scripture in favour of their own traditions did not originate with the historical Jesus, but suggest later polemics. Jesus’ stance on purity is perhaps better characterized as prophetic than halakic.